The Impact of Remuneration and Training on Worker Performance at the Regional Tax and Levy Management Agency of North Sumatra - Sitompul, Melva Melany; Piter, Jhon; Sisilia, Mariska (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
The North Sumatra Regional Tax and Levy Management Agency oversees the management of taxes related to motor vehicles and watercraft, the tax for underground water extraction and utilization, the vehicle name transfer duty, and various other revenue streams. It also acts as a coordinator within the regional revenue sector. Research methods can be understood as a systematic approach to gathering reliable data intended to be discovered, enhanced, and verified, allowing for better comprehension and resolution of issues within the business sector. According to the findings of this research, it is evident that Compensation has a significant impact on Employee Performance at the Regional Tax and Levy Management Agency. In the realm of Compensation, an incentive structure connects pay with individual performance. Workers are rewarded through Compensation for their performance rather than their length of service or the total hours they have worked. Based on the data analysis and collection outcomes, Compensation has a significant simultaneous impact on Employee Performance at the Regional Tax and Levy Management Agency. The training partially impacts employees' performance at the Regional Tax and Levy Management Agency. The performance of employees does have a significant partial effect on their overall performance at the Regional Tax and Levy Management Agency.